The Role of Corporate Governance in Predicting Resilience and Growth During Pandemic Covid-19 - Lelasari Sijabat; Lovenia Marlien Sakul; Fanny Soewignyo (Cakrawala Repositori IMWI, 2024)
We examine the relationship between corporate governance, company resilience, and firm growth that occurred amid the COVID-19 epidemic. We conducted a comprehensive analysis of food and beverage companies listed on the Indonesian stock exchange over a three-year period, spanning from 2020 to 2022. Out of the total of 84 firms in the food and beverage industry, we utilized 68 firm as our final sample. This study utilizes panel data regression to analyze the correlation between corporate governance and the ability of a corporation to withstand challenges and achieve growth in particular situations. An organization that upholds a just and equitable framework of corporate governance demonstrates greater resilience in the face of the COVID-19 pandemic. Studies have indicated that corporate governance does not have a substantial impact on the ability of a company to withstand and recover from challenges or disruptions. Corporate governance does not impact the selected indicators used to assess corporate growth, which include sales growth, asset growth, and profitability measured by return on assets (ROA).